Children of the crisis: ethnographic perspectives on unaccompanied refugee youth in and en route to Europe. Issue 2 (25th January 2020) - Lems, Annika; Oester, Kathrin; Strasser, Sabine
ABSTRACT: This special issue explores the ways unaccompanied refugee youth in and en route to Europe actively deal with the intensification of exclusionary practices towards migrants and refugees. In the Introduction we aim to set the scene for the individual articles by sketching the various political, historical and discursive levels at which the unaccompanied minor has come to be constructed as a crisis figure in Europe. We show how the sense of exceptionality attached to this figure translates into ambiguous and at times extremely contradictory social practices that have far-reaching effects on the lives of refugee youth. In paying attention to the conceptual flaws and dangers inherent in linking unaccompanied minors to ideas of crisis, we aim to demonstrate the importance of taking seriously the ways young people themselves make sense of the ascriptions, ideas and practices they are subject to. We suggest that ethnographically driven research that lays the focus on the ways young people actively navigate the ambiguous social landscapes they are confronted with can form an important means to move beyond the simplistic and ahistorical models of explanation put forward by frameworks of crisis.